Analisis Pertanggungjawaban Pelaku Tindak Pidana Penggelapan Pajak (Studi Putusan Nomor: 10/Pid.Sus/2022/PN.Kbu) - Abadi, Nikmat; Delta, Ria; Januri, Januri (Universitas Sang Bumi Ruwa Jurai, 2025)
This study aims to analyze the legal accountability of perpetrators of tax evasion crimes as stated in Decision Number 10/Pid.Sus/2022/PN.Kbu and examine the judges' considerations in rendering the verdict. The research employs a normative juridical and empirical juridical approach, utilizing primary and secondary data, including primary, secondary, and tertiary legal materials. Data collection was conducted through literature studies and field studies using interviews with Public Prosecutors at the North Lampung District Attorney's Office, selected through purposive sampling. The collected data were analyzed qualitatively using a descriptive approach with inductive reasoning. The findings indicate that the defendant in Decision Number 10/Pid.Sus/2022/PN.Kbu was legally and convincingly proven guilty of violating Article 39 Paragraph (1) letter i of Law Number 6 of 1983 jo. Law Number 16 of 2009, resulting in a sentence of 1 year and 8 months of imprisonment and a fine amounting to twice the unpaid tax. The judges' considerations in reaching the verdict were based on the presented evidence, witness and expert testimonies, as well as aggravating and mitigating factors